2020
DOI: 10.1177/1369433220927281
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on optimum shape of steel slit dampers

Abstract: Steel slit dampers are among the passive energy dissipating devices that have been proposed to improve seismic performance of steel structures. Several experimental and numerical studies have also been carried out to investigate capacity of the dampers in energy dissipation. In this article, a numerical model is developed to obtain optimum boundary shape of the dampers. To achieve this, isogeometric analysis method is utilized as a powerful tool in precise modeling of complex geometries for the purpose of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…These findings are consistent with those of previous studies on slit dampers in the literature. The previous research revealed that utilizing a tapered shape can enhance energy dissipation by approximately 37% compared to the conventional initial shape in literature [85] and around 12~50% in the literature [86].…”
Section: Energy Dissipation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies on slit dampers in the literature. The previous research revealed that utilizing a tapered shape can enhance energy dissipation by approximately 37% compared to the conventional initial shape in literature [85] and around 12~50% in the literature [86].…”
Section: Energy Dissipation Analysismentioning
confidence: 99%
“…The device's energy dissipation capacity and fatigue resistance under low cycling conditions were significantly enhanced by incorporating this configuration. In addition, A numerical model was used by Aminzadeh et al [86] to obtain optimal boundary shapes for slit dampers. They employed the iso-geometric analysis method, allowing precise modeling of complex geometries for nonlinear damper analysis.…”
Section: Application Of the Steel Slit Damper In Braced Framesmentioning
confidence: 99%
“…In addition, the problem definition could include a smoother function for the boundaries that generate better computational modeling of the devices and a reduction in the number of variables [17]. The possibility of using a computer-aided design to create shapes and isogeometric analysis has increased the feasibility of obtaining better devices [18]. In brief, a correct definition of the stress state plays a critical role in the optimization process.…”
Section: Introductionmentioning
confidence: 99%
“…SSD dampers should be embedded in a structure such a way that they sustain plastic behavior before the structural elements (Aghlara and Tahir, 2018; Aminzadeh et al, 2020; Bayat and Shekastehband, 2019). While the SSD dampers are required to be mounted on secondary structures such as bracing systems for vibration dissipation of the structures (Amiri et al, 2018; Lee et al, 2015; Teruna et al, 2015), BRB dampers are directly integrated with the primary structural system.…”
Section: Introductionmentioning
confidence: 99%